A randomized, open phase IV exploratory clinical trial to evaluate the efficacy and safety of acupuncture on the outcome of induction of ovulation in women with poor ovarian response: A study protocol for a randomized controlled trial. Issue 34 (August 2018) - Lee, Hoyoung; Choi, Tae-Young; Shim, Eun Hyoung; Choi, Jiae; Joo, Jong Kil; Joo, Bo Sun; Lee, Myeong Soo; Choi, Jun-Yong; Ha, Ki-Tae; You, Sooseong; Lee, Kyu Sup
Abstract: Introduction: Women with infertility who have a poor ovarian responder (POR), characterized by a low number of retrieved oocytes after ovulation induction, often have a significantly reduced pregnancy rate after in vitro fertilization-embryo transfer (IVF-ET), due to the few transferred embryos. Acupuncture is a form of Korean Traditional Medicine. It involves the insertion of a microscopic needle at a specific point in the body, known as an acupuncture point or an acupoint. In this study, our purpose is to investigate how acupuncture affects the retrieval of mature oocytes after ovulation induction in patients with POR. Methods and analysis: This study will be a randomized clinical trial comprising an IVF-ET trial and an IVF-ET trial after acupuncture. Seventy patients will by enrolled and randomly assigned to either of the 2 groups. The study subjects will be required to be diagnosed as having POR. Participants will be divided into 2 groups: IVF-ET single treatment group, and acupuncture and IVF-ET combined treatment group. The study subjects will be required to participate in a 15-week trial involving 16 acupuncture treatments over a period of approximately 2 months before ovulation induction for oocyte retrieval. The primary assessment of all participants will be comparing the number of oocytes. Result: This treatment will be a therapeutic model for POR. Discussion: Our results will provide patients with POR as well as complementary and alternative medicine professionals, such as Korean medicine doctors, about the potential role of acupuncture in the treatment of POR. This will improve the quality of life in women with infertility and provide an important treatment option for patients with POR. Further studies can be performed to determine the optimal treatment for POR.